2018
DOI: 10.1111/ijd.14125
|View full text |Cite
|
Sign up to set email alerts
|

Chronic generalized pruritus without primary skin lesions: a longitudinal prospective observational study

Abstract: Pruritus is among the most common complaints in the field of dermatology. It is also a disturbing symptom of many systemic disorders. Chronic pruritus (CP) refers to the cases of the symptom which last longer than 6 weeks. We conducted a prospective analysis of patients with generalized pruritus without primary skin lesions. All patients underwent primary evaluations and then were followed from 12 to 18 months for further evaluations. Of the 5,127 patients referred to our dermatology clinic, 49 patients with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…In a study comprising 350 individuals, by Ahmed et al [33], itch was reported in 7.1%. Another perspective was chosen by Alizadeh et al [13] who examined 5 127 patients referred to the dermatologic clinic with chronic generalized itch without primary skin lesions -12.5% of them had DM.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study comprising 350 individuals, by Ahmed et al [33], itch was reported in 7.1%. Another perspective was chosen by Alizadeh et al [13] who examined 5 127 patients referred to the dermatologic clinic with chronic generalized itch without primary skin lesions -12.5% of them had DM.…”
Section: Epidemiologymentioning
confidence: 99%
“…According to the International Forum for the Study of Itch (IFSI), the etiologic classification of chronic itch comprises 6 categories: (I) dermatologic, (II) systemic, (III) neurologic, (IV) psychogenic/psychosomatic, (V) mixed, and (VI) others [12]. Most researchers classify itch in diabetes as systemic itch [13], however some authors suggest mixed aetiology of diabetic itch with the additional involvement of both dermatologic and neurologic components [14][15][16]. Diabetes mellitus appears in most lists of the causes of generalized itch but is not common.…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Forum for the Study of Itch (IFSI), we may divide the etiologic classification of chronic itch to 6 categories: (I) dermatologic, (II) systemic, (III) neurologic, (IV) psychogenic/psychosomatic, (V) mixed, and (VI) others [ 4 ]. IFSI classifies itch in diabetes as systemic itch arising on non-inflamed skin or normal-appearing skin [ 5 ]. However, researchers have recently suggested that the etiology of itch in DM is additionally involved with both dermatologic and neurologic components [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a frequent and distressing symptom occurring not only in dermatologic conditions but also in chronic systemic diseases [ 5 , 6 ], posing a high burden and decrease in quality of life (QoL) of patients [ 7 , 8 ]. Most researchers classify itch in diabetes, according to the International Forum for the Study of Itch (IFSI), as systemic itch [ 9 ]; however, some authors suggested mixed etiology of diabetic itch with the additional involvement of both dermatologic and neurologic components [ 10 12 ]. Only a few studies investigated the occurrence of itch in DM, reporting a wide prevalence ranging from 18.4–27.5% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%